2003
DOI: 10.1002/humu.10233
|View full text |Cite
|
Sign up to set email alerts
|

One gene, two phenotypes:ROR2 mutations in autosomal recessive Robinow syndrome and autosomal dominant brachydactyly type B

Abstract: Autosomal recessive Robinow syndrome (RRS) is a severe skeletal dysplasia with short stature, generalized limb shortening, segmental defects of the spine, brachydactyly, and a dysmorphic facial appearance. The gene encoding receptor orphan receptor tyrosine kinase 2 (ROR2) is located on chromosome 9q22 and homozygous loss-of-function mutations in this gene are responsible for RRS. Moreover, knocking out the mouse Ror2 gene causes mesomelic dwarfism in the homozygous state, with almost identical features to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 87 publications
2
76
0
Order By: Relevance
“…I 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 21 20 19 18 17 16 15 14 13 12 11 10 9 8 7 6 5 4 To date, eight different pathogenic ROR2 mutations have been reported in a total of 14 families with BDB1. [1][2][3][6][7][8] These mutations are believed to have a specific gain-of-function effect, not a simple haploinsufficiency. 1,3 All the documented BDB1-causing ROR2 mutations are nonsense or frameshift and are located in the last two exons or in the last intron, 1-3,6-8 enabling the mutant mRNAs to escape degradation by nonsense-mediated decay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…I 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 21 20 19 18 17 16 15 14 13 12 11 10 9 8 7 6 5 4 To date, eight different pathogenic ROR2 mutations have been reported in a total of 14 families with BDB1. [1][2][3][6][7][8] These mutations are believed to have a specific gain-of-function effect, not a simple haploinsufficiency. 1,3 All the documented BDB1-causing ROR2 mutations are nonsense or frameshift and are located in the last two exons or in the last intron, 1-3,6-8 enabling the mutant mRNAs to escape degradation by nonsense-mediated decay.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][6][7][8] These mutations are believed to have a specific gain-of-function effect, not a simple haploinsufficiency. 1,3 All the documented BDB1-causing ROR2 mutations are nonsense or frameshift and are located in the last two exons or in the last intron, 1-3,6-8 enabling the mutant mRNAs to escape degradation by nonsense-mediated decay. 12 The five distal mutations clustered between the intracellular tyrosine kinase domain and the first serine/threonine-rich domain cause a more severe phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with recessive Robinow syndrome (RRS) characterized by mesomelic limb shortening, dwarfism, shortened genitalia and brachydactyly are homozygous for null alleles in the Ror2 gene. [44][45][46] Individuals that are heterozygous for C-terminal truncations of Ror2 exhibit a dominant disorder called Brachydactyly type B (BDB1), manifested by a shortening of the phalanges. 47,48 Recently, it was shown that a dominantly heritable disorder that is indistinguishable from RRS was due to mutations in conserved cysteines of the Wnt5a gene.…”
Section: 28mentioning
confidence: 99%